Respiratory heat loss in the sheep: a comprehensive model - da Silva, R. G.; LaScala, N.; Lima, A. E.; Catharin, M. C. (Springer, 2002)
A model is presented for the respiratory heat loss in sheep, considering both the sensible heat lost by convection (C-R) and the latent heat eliminated by evaporation (E-R). A practical method is described for the estimation of the tidal volume as a function of the respiratory rate. Equations for C-R and E-R are developed and the relative importance of both heat transfer mechanisms is discussed. At air temperatures up to 30 degreesC sheep have the least respiratory heat loss at air vapour pressures above 1.6 kPa. At an ambient temperature of 40 degreesC respiratory loss of sensible heat can be nil; for higher temperatures the transfer by convection is negative and thus heat is gained. Convection is a mechanism of minor importance for the respiratory heat transfer in sheep at environmental temperatures above 30 degreesC. These observations show the importance of respiratory latent heat loss for thermoregulation of sheep in hot climates.
Keywords: Sheep; respiratory heat loss; evaporation; convection; tidal volume